Sapper Martin the secret Great War diary of Jack Martin - Martin, Jack (Bloomsbury Publishing Plc, 2009)
Albert John ('Jack') Martin was a thirty-two-year-old clerk at the Admiralty when he was called up to serve in the army in September 1916. These diaries, written in secret, hidden from his colleagues and only discovered by his family after his return home, present the Great War with heartbreaking clarity, written in a voice as compelling and distinctive as Wilfred Owen or Siegfried Sassoon and all the more extraordinary given that it is not an officer's but that of a private. From his arrival in France and his participation in the Somme, through offensives at Ypres and eventual demobilisation after the Armistice, we see wartime life as it really was for the ordinary Tommy. In these journals, introduced and edited by bestselling First World War historian Richard van Emden, we witness the cheerful Albert Martin getting to grips with life in the trenches and, together with his comrades in the Royal Engineers, confronting the ever-present threat of injury and death. We also see the mundane reality of life at the front line - the arguments with superiors, the joy brought by the arrival of packages from loved ones at home and the appalling conditions in which that attritional war was fought.